Perancangan Interior Pusat Kebugaran Jasmani Anak di Surabaya - Hardjawikarta, Jovita (Intra, 2014)
This design project is about a Sport Centre for Children. The background of the birth of this idea is that children can get an education in Surabaya completely and perfectly, not only intellectually increase in intelligence but also can develop in motor development that can help children to be more confident and Â have a healthy lifestyle since the early age. The theme of this design is